Allogenic mouse cell vaccine inhibits lung cancer progression by inhibiting angiogenesis - Jun Zhao; Xiaoling Zhang; Yunyi Du; Lurong Zhou; Ziming Dong; Jimin Zhao; Jing Lu (Taylor & Francis Group, 2021)
Aim: This research investigated the therapeutic effect of an allogeneic mouse brain microvascular endothelial cell vaccine on lung cancer and further elucidated its potential anti-angiogenic mechanism. Materials & methods: The immune effect of the allogeneic bEnd.3 vaccine and DC vaccine loaded with bEnd.3 antigen on the subcutaneous transplantation of Lewis lung cancer (LLC) was assessed by ELISA, the CCK test and the CTL killing test. The mechanism was preliminarily revealed by immunohistochemistry and immunoblot analysis. Results: This study revealed that tumor volume was decreased (p < .01) and the survival was prolonged significantly (p < .05) by the bEnd.3 vaccine in subcutaneous LLC transplantation in the vaccine prevention group. In contrast, both tumor volume in the serum therapeutic group and survival of bEnd.3 vaccine were not significantly different from those of the control group (p > .05). Importantly, tumor volume and survival of the T lymphocyte therapeutic group were decreased and prolonged (p < .05). In addition, both tumor volume and survival of DC vaccine loaded with bEnd.3 in the vaccine prevention group were decreased and prolonged significantly (p < .01). Furthermore, bEnd.3 vaccine and DC vaccine loaded with bEnd.3 both produced the activity of killing bEnd.3 target cells in vitro.The reason may induce the immune mice to produce anti-VEGFR-II, anti-endoglin and anti-integrin αν antibodies to have an anti-angiogenesis function. Conclusion: The allogeneic mouse bEnd.3 cell vaccine can block angiogenesis and prevent the development of lung cancer transplantation tumors.